Effectiveness of Unilateral Training of the Uninjured Limb on Muscle Strength and Knee Function of Patients With Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis of Cross-Education - Cuyul Vásquez, Iván.; Álvarez, Eliana; Riquelme, Ariel; Zimmermann, Rocio; Araya Quintanilla, Felipe. (NLM (Medline), 2022)
Context: Unilateral training of the uninjured limb could be a useful therapeutic tool to induce cross-education in periods of immobilization, however, the effectiveness of this training in patients with anterior cruciate ligament (ACL) reconstruction is unknown. Objective: To determine the effectiveness of unilateral training of the uninjured limb on muscle strength and knee function in patients with ACL reconstruction. Design: Systematic review and meta-analysis. Evidence acquisition: An electronic search was performed in the MEDLINE, LILACS, CENTRAL, Embase, Scopus, Web of Science, CINAHL, SPORTDiscus, and PEDro databases from inception until March 2021. The authors included randomized clinical trials that evaluated the effectiveness of unilateral training of the uninjured limb on muscle strength and knee function in patients after ACL reconstruction. Evidence synthesis: Seven clinical trials met the eligibility criteria, and for the quantitative synthesis, 5 studies were included. The standardized mean difference for isometric quadriceps strength was 0.60 at 8 to 12 weeks (95% confidence interval, 0.29 to 0.92; P = .01; I2 = 6%). There was a high quality of evidence according to the Grading of Recommendation, Assessment, Development and Evaluation rating. Four studies assessed knee function through different self-administered questionnaires at 8, 24, and 26 weeks. Only one study reported significant differences in knee function at 8 weeks, favoring the unilateral training group. Conclusions: There was a moderate to high quality of evidence, with statistical significance that the addition of unilateral training to standard rehabilitation improved the cross-education of quadriceps strength after ACL reconstruction. More research is needed to assess the consistency of these results. International Prospective Register of Systematic Reviews registration number: CRD4202019995
Keywords: Cross-training; Exercise therapy; Anterior cruciate ligament injuries